Green supply chain management - Food for thought? - Habib, Farooq; Ali, Abdul; Bentley, Yongmei; Cao, Guangming (Taylor & Francis, 2016)
This paper investigates the impact of green supply chain management (GSCM) practices on the performance of UK food retail small and medium-sized enterprises (SMEs). A quantitative approach using a non-probability sampling of 84 participants was employed. Based on the literature review, five hypotheses were developed and tested using the partial least square-structural equation modeling (SEM-Smart PLS 2.03) approach. The reviewed literature revealed that key internal drivers (ID) and external pressures (EP) stimulate organizations to initiate GSCM practices in UK food retail SMEs. Though empirical findings strongly supported the statement that ID influence GSCM practices, they did not show a significant relationship between EP and GSCM practices. Literature also suggests that practicing GSCM can help improve the efficiency, brand image (BI) and profitability, and thus improve the overall firm performance which is also empirically proved. This study helps enrich existing theories on SCM and organizational performance. As to practical impact, this study should facilitate SMEs in GSCM practices and thus help green the economy. While the findings of this study have limited generalisability as the data were collected from UK SMEs only and the sample size was comparatively small, this research establishes a foundation for further study in this domain.
Keywords: Green supply chain management; Food retail; Small and medium-sized enterprise; Performance; Sustainable supply chain; UK